SISTEM INFORMASI PENJUALAN MAINAN PADA NOGO SHOP SEMRARANG - ZULFIKHAR RUSDIYANTO, 12.01.55.0048 (Information Technology and Telematics, 2017)
Abstract The use of technology have effected people incommunication which can made the activity become easier and improve human works.  A good informastion is depends on the due time and the relevant of the informations. In the trading bussiness, internet technology made the selling and purchasing process become easier. E-commerce system is a kind of public service in a form of web which contains list of product and completed with the order and purchasing form. This e-commerce system design was made to help customer in purchasing on Nogoshop and made it easier form the owner to handle in every order and purchasing transaction, and also to checked at the purchasing report. This system can be developed by the user with participate in giving opinion which can improve purchasing transaction and interaction process between the customer and the seller bu using system.Keyword : e-commerce system, design, nogohsop, purchasing transaction